NURSING THEORY APPLICATION OF NEED FOR HELP AND UNPLEASANT SYMPTOMS IN THE ABORTUS INKOMPLIT CASE - Ira Sukyati; Setyowati Setyowati; Wiwit Kurniawati (JURNAL KEPERAWATAN CIKINI, 2021)
Maternal deaths are mostly caused by bleeding, hypertension in pregnancy, infections, old / stuck particles and abortion. The main complaint of pregnant women who experience abortion is bleeding that occurs in the acute phase, it can threaten the safety of the mother's life. Not only cause physical impact, but can result in psychological effects of stress, anxiety, depression and grief. Gradually someone will adjust to the process of grieving. In giving nursing care with abortus incomplete used the theory of nursing need for help in the acute phase consisting of three activities of identification, ministration, validation and evaluation, while in the healing phase of post-action curettes used noses sympomps theory more focused on the symptoms experienced , which consists of three concepts namely physiological, psychosocial and situational. The results show that both models can be effectively applied to the five cases of women with incomplete abortion.